Note-taking in consecutive interpreting. On the reconstruction of an individualised language - Kohn, Kurt; Albl-Mikasa, Michaela (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
To facilitate the process of consecutive interpreting, professional interpreters typically use a special system of note-taking. In the approaches developed on the basis of practical interpreting experience, these notations are commonly regarded as a note-taking technique, and in relevant specialist literature they are often conceived as a language-independent instrument. Against the background of a cognitive approach, however, it can be shown that the so¬called note-taking TECHNIQUE can adequately be described by means of the theoretical constructs LANGUAGE and DISCOURSE. The language dimension is explored with regard to word meanings, word formation and inflection, semantic relations at sentence and text level as well as pragmatic functions. The discourse dimension is mainly discussed from the perspective of rele¬vance theory with a particular emphasis on the balance between the explicit and the implicit.